2019
DOI: 10.1080/23311908.2019.1568069
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical time and space interference in Tau and Kappa effects

Abstract: How are the domains of space and time related? One approach, A Theory of Magnitude (ATOM), proposes an undifferentiated system of magnitude representation in the brain, predicting that space and time are symmetrically related, while Conceptual Metaphor Theory (CMT) proposes that we represent time using spatial metaphors, predicting asymmetrical interactions between domains. Tau and Kappa effects are perceptual phenomena that arise when observers judge the distance/duration between consecutive stimuli in sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…The current results are adding to the debate on ATOM (Walsh, 2003) and CMT (Lakoff & Johnson, 1980). In contrast to previous research applying tau and kappa paradigms to solve the controversy between those theories (Reali et al, 2019), the current results clearly contradict the asymmetrical relationship proposed in CMT with higher impact of spatial characteristics on temporal Rather than finding a symmetrical or asymmetrical relationship between spatial and temporal representations, the size of effects in either direction may actually depend on other factors. Here, we showed that sensory modality is one of those factors.…”
Section: Debate On Atom Versus Cmtcontrasting
confidence: 99%
See 1 more Smart Citation
“…The current results are adding to the debate on ATOM (Walsh, 2003) and CMT (Lakoff & Johnson, 1980). In contrast to previous research applying tau and kappa paradigms to solve the controversy between those theories (Reali et al, 2019), the current results clearly contradict the asymmetrical relationship proposed in CMT with higher impact of spatial characteristics on temporal Rather than finding a symmetrical or asymmetrical relationship between spatial and temporal representations, the size of effects in either direction may actually depend on other factors. Here, we showed that sensory modality is one of those factors.…”
Section: Debate On Atom Versus Cmtcontrasting
confidence: 99%
“…A useful testbed for independent manipulations might lie in two perceptual illusion effects, called tau and kappa effects (Abe, 1935 ; Benussi, 1913 ; Cohen et al, 1953 ; Gelb, 1914 ; Helson & King, 1931 ). Previous research has already identified these effects as promising tools to test ATOM against CMT (Alards-Tomalin et al, 2014 ; Reali et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%